2010
DOI: 10.1074/jbc.m110.170076
|View full text |Cite
|
Sign up to set email alerts
|

Brain Fatty Acid-binding Protein and ω-3/ω-6 Fatty Acids

Abstract: Malignant gliomas (MG) are highly infiltrative tumors that consistently recur despite aggressive treatment. Brain fatty acid-binding protein (FABP7), which binds docosahexaenoic acid (DHA) and arachidonic acid (AA), localizes to sites of tumor infiltration and is associated with a poor prognosis in MG. Manipulation of FABP7 expression in MG cell lines affects cell migration, suggesting a role for FABP7 in tumor infiltration and recurrence. Here, we show that DHA inhibits and AA stimulates migration in an FABP7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 56 publications
3
75
0
Order By: Relevance
“…FABP5 RT-PCR products could be generated in low levels from U251 cell RNA, in the presence or absence of RA treatment, but the FABP5 protein was undetectable (Figure 3A and 3B). These results are supported by a previous study [24]. DNA sequencing confirmed that the 281 bp RT-PCR product was amplified with FABP5 primers and was specifically generated from FABP5 transcripts, which encompassed Exon 1 to Exon 3 (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…FABP5 RT-PCR products could be generated in low levels from U251 cell RNA, in the presence or absence of RA treatment, but the FABP5 protein was undetectable (Figure 3A and 3B). These results are supported by a previous study [24]. DNA sequencing confirmed that the 281 bp RT-PCR product was amplified with FABP5 primers and was specifically generated from FABP5 transcripts, which encompassed Exon 1 to Exon 3 (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…The mRNA of Fabp7, mainly detected in brain, was included in our study because this member of the Fabp family was occasionally detected in the zebrafish (Danio rerio) testis (Liu et al 2003) and because it is involved in the transport of the 22-carbon PUFA-like docosahexaenoic acid (Balendiran et al 2000, Mita et al 2010. This fatty acid, like docosapentaenoic acid, abounds in mouse testis lipids (Furland et al 2003), where it is highly concentrated in membrane GPLs and TAGs, of germ cells and RB (present results).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms by which DHA can directly affect the invasive phenotype of cancer cells remain unclear. AA has promigratory and tumour growth properties 96 , which can be antagonized by DHA 97,98 . It has been suggested that the relative levels of DHA and AA in the tumour environment might have a profound impact on tumour growth properties.…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%